Financialisation and Real Investment in the European Union Using a Country-Level Analysis: Beneficial or Prejudicial Effects? - Barradas, R. (Dinâmia’CET-IUL Working Paper Nº 2015/10, 2015)
This paper makes an empirical assessment of the relationship between financialisation and real investment by non-financial corporations using panel data composed of 27 European Union countries over 19 years (from 1995 to 2013). On one hand, financialisation leads to a rise in financial investments, deviating funds from real investments (“crowding out” effect). On the other, pressures from shareholders to intensify financial payments restrict the funds available for new real investments. We estimate an aggregate investment equation with the traditional variables (profitability, debt, cost of capital, savings rate and output growth) and two further measures of financialisation (financial receipts and financial payments). Findings show that financialisation has damaged real investment in European Union countries, mainly through the channel of financial payments either in interest or dividend payments. It is also found that the prejudicial effects of financialisation in investment are more marked in more financialised countries. In addition, it is concluded that debt has a harmful effect on real investment as the increasing levels of non-financial corporations' indebtedness prevent the use of new debts to finance real investments.